2013
DOI: 10.1007/s13300-013-0024-0
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Tolerability of Sitagliptin in Type 2 Diabetes: Pooled Analysis of 25 Clinical Studies

Abstract: IntroductionIn a previous pooled analysis of 19 double-blind clinical studies conducted by Merck, which included data available as of July 2009 on 10,246 patients with type 2 diabetes (T2DM), treatment with sitagliptin was shown to be generally well tolerated compared with treatment with control agents. As the sitagliptin clinical development program continues, additional studies with sitagliptin have been completed. The present analysis updates the safety and tolerability assessment of sitagliptin by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
89
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 63 publications
17
89
0
3
Order By: Relevance
“…When the background medication included a sulfonylurea, the rates of hypoglycaemia were higher and similar in both groups, as expected due to the influence of this class of agent 14, 15, 16. With regard to the small increase in the observed incidences of abdominal pain and vomiting with sitagliptin compared with dapagliflozin, and of edema peripheral with dapagliflozin compared with sitagliptin, imbalances of this type have not previously been noted in pooled safety analyses of either treatment 17, 18…”
Section: Discussionsupporting
confidence: 66%
“…When the background medication included a sulfonylurea, the rates of hypoglycaemia were higher and similar in both groups, as expected due to the influence of this class of agent 14, 15, 16. With regard to the small increase in the observed incidences of abdominal pain and vomiting with sitagliptin compared with dapagliflozin, and of edema peripheral with dapagliflozin compared with sitagliptin, imbalances of this type have not previously been noted in pooled safety analyses of either treatment 17, 18…”
Section: Discussionsupporting
confidence: 66%
“…Two meta-analyses suggested that the DPP-4 inhibitors are associated with reduced CV risk (23,24). Importantly, however, these data were obtained predominantly from relatively small and/or short-term investigations (18,19,30), systematic reviews (21,28,29), and pooled analyses (20,22,(25)(26)(27)31,32) in by-and-large younger and healthier study participants with very limited, and generally unadjudicated, CV safety information.…”
Section: Discussionmentioning
confidence: 99%
“…Since that date the use of dipeptidyl peptidase-4 (DPP-4) inhibitors for the management of type 2 diabetic patients has increased. Continued assessment of adverse events of sitagliptin reported from clinical trials and post--marketing environment is ongoing [14]. Pioglitazone (a thiazolidinedione) acts as an insulin sensitizer and is used for treating type 2 diabetes [15].…”
Section: Introductionmentioning
confidence: 99%